The Implementation of Discovery Learning with Sequential Picture Puzzle to Improve Elementary Students’ Writing Literacy Skills - Agustin, Putri Prihandini; Siswoyo, Andika Adinanda; Saliana, Silvi Milata; Dhani , Izzatul Maulidha Rama (Actual Insight, 2025)
Writing literacy skills is one of the essential skills that must be developed from an early age in elementary education. This study aimed to develop students’ narrative writing literacy skills through the implementation of the Discovery Learning model assisted by Sequential Picture Puzzle media in Grade IV of Socah 2 Public Elementary School. The research problem addressed was the low narrative writing ability of students. The approach used was Classroom Action Research, referring to the spiral model of Kemmis and McTaggart, conducted in two cycles. The research subjects were 27 fourth-grade students. Data collection techniques included observation and documentation. Data were analyzed using descriptive quantitative methods based on seven aspects of narrative writing assessment. The results showed a significant improvement in students’ narrative writing literacy skills. Classical learning mastery increased from 55.6% in Cycle I to 77.78% in Cycle II, with the average score rising from 67.81 to 72.33. The most notable improvements were found in sentence coherence and the accuracy of spelling and punctuation. The Sequential Picture Puzzle media proved to be an effective visual aid in stimulating students to organize story ideas sequentially and systematically. Therefore, the integration of the Discovery Learning model with visual media contributes positively to the development of elementary students’ narrative writing literacy and serves as an innovative alternative strategy in literacy education.